Association between periodontal health status and patient‐reported outcomes in patients managed in a non‐specialist, general dental practice. (5th November 2018) - Sharma, Praveen; Yonel, Zehra; Busby, Michael; Chapple, Iain L.; Dietrich, Thomas
Abstract: Aims: To explore the associations between periodontal status and patient‐reported outcomes (PROs) in a large cohort of patients based in non‐specialist general dental practice. Materials and methods: Analysis was conducted using data from 14, 620 patients, in 233 non‐specialist dental practices across the UK. As part of routine clinical care, data on periodontal probing depths (PPD), alveolar bone loss (ABL), bleeding on probing (BoP) as well as PROs (oral pain/discomfort, dietary restrictions and dental appearance) were recorded using an online database. The associations between periodontal status and PROs were investigated using logistic regression analysis, adjusting for confounders. Results: We found a positive association between worse periodontal health and the prevalence of PROs. After adjustment for confounders, 13.8% of patients in the healthiest category (PPD < 5 mm, ABL < 2 mm, no BoP) reported pain/discomfort, compared to 20.7% of patients in the worst category (PPD > 7 mm, ABL > 4 mm). A similar trend was seen with reporting a restricted diet and unhappiness with appearance. Conclusion: This study provides novel insights into the associations between periodontal status and PROs in a non‐specialist, general dental practice, highlighting the benefits of prevention and management of periodontitis.